PELATIHAN PEMBUATAN MULTIMEDIA INTERAKTIF BERBASIS TEKNOLOGI UNTUK MEMFASILITASI PEMBELAJARAN TERDIFERENSIASI KURIKULUM MERDEKA - Arif Bulan; Ija Srirahmawat; Hasan Hasan (Universitas Mataram, 2023)
This community service (CS) activity is motivated by the results of an initial study that many English teachers in Dompu district do not know the concept of differentiated learning in the independent curriculum and have never received training on learning multimedia. In addition, teachers do not understand the concept and implementation of differentiated learning, teachers still use conventional teaching approaches, media and methods without involving or using learning multimedia. And finally, teachers have never attended training on making and developing interactive learning multimedia, let alone technology-based. The aim of this CS is to provide training in making technology-based interactive multimedia to facilitate differentiated learning of the independent curriculum which is divided into four main activities. The method of this CS activity includes the preparation stage of the programme which includes situation analysis, needs and preparation of training needs. Furthermore, the implementation stage includes activities to provide training materials. And the last is the monitoring and evaluation stage and the sustainability of the programme which includes collecting data on the results of training and follow-up. There are four results of this CS activity, first, training has been organised in the form of providing training materials on the independent curriculum, differentiated learning and interactive learning multimedia. Second, training has been held to increase teacher expertise in making differentiated learning materials in accordance with the independent curriculum. Third, a workshop on making technology-based interactive learning multimedia has been held. Fourth, there has been assistance in making interactive learning multimedia for partners. The conclusion of the CS is that there is an increase in the knowledge and skills of CS partners, in this case English teachers who are members of the first school subject teacher meeting regarding the independent curriculum, differentiated learning, interactive multimedia and independent curriculum teaching tools.